2020
DOI: 10.1136/bmjopen-2020-036915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creative Expressive Arts-based Storytelling (CrEAS) programme on older adults with mild cognitive impairment: protocol for a randomised, controlled three-arm trial

Abstract: IntroductionEarly non-pharmacological interventions can prevent cognitive decline in older adults with mild cognitive impairment (MCI). Creative expression (CrExp) can potentially mitigate cognitive decline and enhance the physical and mental health of older people. However, it is unclear whether activities involving CrExp can improve cognitive function and other health-related outcomes in older adults with MCI. The aim of the present study is to develop a Creative Expressive Arts-based Storytelling (CrEAS) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In addition, it has been shown that the glycemic variable and hypertension are associated with dementia-like diseases such as progressive supranuclear palsy, Alzheimer’s disease, and corticobasal syndrome [ 4 , 5 ]. MCI is known as a neurological disorder that is somewhere between normal functioning and dementia [ 6 ] and is defined by the WHO as a disorder characterized by memory impairment, learning difficulties, and reduced ability to concentrate on a task for more than brief periods [ 7 ]. The prevalence of MCI increases with age and has an incidence ranging from 21.5 to 71.3 cases per 1000 inhabitants/year [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that the glycemic variable and hypertension are associated with dementia-like diseases such as progressive supranuclear palsy, Alzheimer’s disease, and corticobasal syndrome [ 4 , 5 ]. MCI is known as a neurological disorder that is somewhere between normal functioning and dementia [ 6 ] and is defined by the WHO as a disorder characterized by memory impairment, learning difficulties, and reduced ability to concentrate on a task for more than brief periods [ 7 ]. The prevalence of MCI increases with age and has an incidence ranging from 21.5 to 71.3 cases per 1000 inhabitants/year [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of cognitive impairment, the benefits of cognitive intervention in improving cognitive function in old adults with MCI or dementia have been widely reported (Chan et al ., 2017; Marlats et al ., 2019; Savulich et al ., 2017; Steinbeisser et al ., 2020). Novel cognitive intervention therapy such as TimeSlips showed positive effects in target population (Kim et al ., 2020; Lin et al ., 2020). The creative expression program (CrExp), which is based on the concepts of art therapy, showed that when the patients were immersing in a group-centered activity, it may specifically benefit one’s emotional expression and communication skills in older adults with AD or dementia (Shimada et al ., 2017; Vigliotti et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In creating digital stories about their life histories, Hausknecht et al (2019) claimed that older adults are given a chance to engage with others through stories as digital producers. In fact, Lin et al (2020) proposed that such creative retelling of past life events has the capability to improve older people's physical and mental health and slow down their intellectual deterioration. Hence, storytelling is now a standard psychotherapeutic intervention that has become a vital tool in the arsenal of mental health recovery services (Nurser et al, 2018).…”
mentioning
confidence: 99%
“…Telling stories is a time-tested method of creatively narrating, translating, and communicating lived experiences of individual people or communities in various human contexts (Davis & Restrepo, 2003; Grove, 2015; Lin et al, 2020; McNett, 2016). Indeed, storytelling is a popular form of art by which cultural messages and myths are recreated and transmitted intergenerationally (Davis & Restrepo, 2003; Sawyer & Willis, 2011).…”
mentioning
confidence: 99%